The effects of weather on physical activity and sedentary behaviour in older adults - Kathryn M. Crosby; Kathryn M. Crosby; Kathryn M. Crosby; Brittany Adams; Elizabeth Zambrano Garza; Mathieu L. Bourbonnais; Melanie Fenton; Christiane Hoppmann; Christiane Hoppmann; Christiane Hoppmann; Jennifer M. Jakobi; Jennifer M. Jakobi; et al. (Frontiers in Sports and Active Living)
BackgroundMany older adults do not meet current physical activity (PA) guidelines, and this might be influenced by environmental factors (e.g., temperature). The purpose of this study was to determine how various weather variables influence light PA (LPA), moderate-vigorous PA (MVPA), and sedentary behaviour (SB), steps, and time spent walking outdoors.MethodsFifty community-dwelling older adults completed the 10-day assessment period, using a Fitbit fitness tracker, Global Position System (GPS), and completing self-report questionnaires. Forty participants were included in the analysis. LPA, MVPA, and SB were calculated using heart rate and multilevel models were used to assess their association with weather variables.ResultsNumber of steps was positively associated with self-reported health status (0.18, p < 0.01). Increased age was associated with less time spent engaging in LPA (total and outdoors), reduced steps, increased time spent sedentary, and less time spent walking outdoors. LPA outdoors was positively associated with mean temperature. Freeze thaw cycles were associated with time spent walking outdoors. Females spent more time in total LPA and LPA indoors, and as age increased total LPA and LPA outdoors decreased.ConclusionsOlder adults located in a dry (∼690 mm precipitation annually) region with warm winters and hot summers (−5°C–30°C) seemingly choose indoor activities. Females tend to participate in indoor LPA, and as age increases the time spent in outdoor LPA decreases.ImplicationsConsideration needs to be given to designing indoor PA interventions, with a focus on increasing MVPA for older adults.